Nutrition Intake and Nutrition Status of Pancreatic Cancer Patients: Cross-Sectional and Longitudinal Analysis of a Randomized Controlled Exercise Intervention Study. (26th November 2022) - Clauss, Dorothea; Rötzer, Ingeborg; Tjaden, Christine; Hackert, Thilo; Wiskemann, Joachim; Steindorf, Karen
Abstract: Pancreatic cancer patients often present with an inadequate nutritional intake. At the same time, there are no standardized recommendations for nutrition intake during and after cancer treatment. In a prospective analysis of a randomized controlled trial analyzing the effects of a 6-month resistance training in pancreatic cancer patients, we assessed the nutritional intake and the impact of a 6-month supervised resistance training or home-based resistance training vs. usual care control on the nutritional intake of the patients. Nutritional intake was assessed by 24-h recall before and after the 6-month resistance training period. At baseline low protein intake (<1 g/kg body weight) was found in 33.9% of the 59 patients and low energy intake (<25 kcal/kg body weight) was found in 39.0% of the patients. In all, 35.6% of the patients were classified with a risk of malnutrition (NRS ≥ 3). In the total of 46 patients who finished the 6-month intervention period, there was no difference in nutritional intake over time between resistance training and usual care control. In conclusion, it appears that the majority of our study population had an adequate protein and energy intake. A resistance training seems to have no influence on the nutritional intake of the patients.